Should Robots Be Like Humans? A Pragmatic Approach to Social Robotics - Budi Hartanto (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2023)
This paper describes the instrumentalizing aspects of social robots, which generate the term pragmatic social robot. In contrast to humanoid robots, pragmatic social robots (PSRs) are defined by their instrumentalizing aspects, which consist of language, skill, and artificial intelligence. These technical aspects of social robots have led to the tendency to attribute a selfhood characteristic or anthropomorphism. Anthropomorphism can raise problems of responsibility and the ontological problems of human-technology relations. As a result, there is an antinomy in the research and development of pragmatic social robotics, considering that they are expected to achieve similarity with humans in terms of completing works. How can we avoid anthropomorphism in the research and development of PSRs while ensuring their flexibility? In response to this issue, I suggest intuition should be instrumentalized to advance PSRs’ social skills. Intuition, as theorized by Henry Bergson and Efraim Fischbein, overcomes the capacity of logical analysis to solve problems. Robots should be like humans in the sense that their instrumentalizing aspects meet the criteria for the value of human social skills.